Comparison of different fluorapatite dip coated layers on porous zirconia tapes - Albano, Maria Patricia (2014)
Fluorapatite (FA) layers with different thickness and microstructures on porous 3 mol% yttria-partially stabilized zirconia (Y-PSZ) substrates have been fabricated by dipping porous zirconia tapes into aqueous fluorapatite slurries. Porous ZrO2 tapes were developed using starch and an acrylic latex as fugitive additive and binder, respectively. Two different binders, poly(vinyl)alcohol (PVA) and latex were used to prepare the fluorapatite dip coating slips. The influence of the suspension properties and the porous structure of the tape surfaces (top and bottom) on the formation rate and consequently on the layer thickness formed on each surface were studied. In addition, the microstructure of the layers produced by using the different dip-coating slips were compared and the osteoblastic cellular response to the different FA coating layers was examined. A greater initial thickness of the layer adhered was found for the tapes dip coated in the FA slip with latex; for immersion times>0, the casting rate was observed to be strongly influenced by both the structure of the tape surfaces and the suspension properties. For both FA slurries, the casting rate at the top surface of the tapes was greater than that at the bottom surface. Sintered layers with thickness 8–9 times greater on both tape surfaces were found using the dip coating slip with latex. For each tape surface, the casting rate was accelerated and the layer shrink during sintering was reduced by using the dip coating slip with latex. The coating layer produced with latex enhanced the osteogenic potential of osteoblastic cells in vitro, which is ultimately an indication of the material׳s capacity to promote bone repair in vivo.